ANTAGONISME ISLAM DAN NEGARA: PENGALAMAN INDONESIA - Muhammad Afkaf (Sharia and Law Faculty, 2017)
This article aims to study on socio-historical perspective of Islam politic in Indonesia. Through this perspective, the author argues that problem of the relation between religion and state has been un- finished. However, the effort to integrate the concepts has been undertaking by scholars, especially in the New Order era. Historically, Islam has been utilised in socio-political power in Indonesia. The present writer examines one of example from the experience of Aceh. This leads the serious discussion among scholars on Islamic political thought which not only focussing on the relation between religion and state, but also the concept of secularism.